A revision of Gerrhopilus inornatus (Squamata: Gerrhopilidae) reveals a multi-species complex - Kraus, Fred (Zootaxa, 2023)
Melanesian blindsnakes of the genus Gerrhopilus have been little collected or researched. I examined specimens assigned in museums to Gerrhopilus inornatus and found considerable morphological diversity among them that indicates the presence of multiple species. I redescribe G. inornatus (Boulenger) based on the holotype and one additional specimen, and I describe six new species among specimens currently subsumed under that name from Papua New Guinea: Gerrhopilus flavinotatus sp. nov., Gerrhopilus lorealis sp. nov., Gerrhopilus papuanorum sp. nov., Gerrhopilus polyadenus sp. nov., Gerrhopilus slapcinskyi sp. nov., and Gerrhopilus wallachi sp. nov. Each species is currently known from only 1–3 specimens, and all but two are known only from single localities. In addition to traditional information on scale counts, habitus, and color patterns, I found the numbers and distributions of epidermal glands among the head shields to be especially useful for discriminating among species. The number of recognized Melanesian Gerrhopilus has increased tremendously in recent years, but the region has been poorly sampled for these snakes, and it is to be expected that additional species will be identified at such time as surveys can more effectively target these cryptic snakes.